La importancia del trabajo no asalariado en la economía urbana - García, Brígida (El Colegio de México A.C., 1989)
The aim of this article is, in the first place, to conduct a succinct review and analysis of various theoretical efforts that have attempted to explain the presence and importance of non-wage labor in urban economies of underdeveloped countries.In the second place, the author provides an overview of Mexico's non-agricultural economy in the medium term (1950-1980), for the purpose of arousing interest in associating the continuation, disappearance, or possible extension of that economy with the rates of growth the country experienced during that period. Special attention is paid to documenting those branches of the Mexican economic structure that have afforded the greatest space for the existence of non- agricultural non-wage labor, as well as to the evolution undergone, in this sense, by the different regions in Mexico.